THE USE OF A STEP-BY-STEP METHOD IN THE CLASSROOM OF THE DISCIPLINE "METHODS OF TEACHING SPECIAL DISCIPLINES" (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
This article actualizes the need to introduce an interactive teaching method into the educational process. The authors give examples of the most common techniques by which positive results can be achieved in the learning process.